Effect of Additional Treatments Combined with Conventional Therapies in Pregnant Patients with High-Risk Antiphospholipid Syndrome: A Multicentre Study - Ruffatti, Amelia; Tonello, Marta; Hoxha, Ariela; Sciascia, Savino; Cuadrado, Maria J.; Latino, José O.; Udry, Sebastian; Reshetnyak, Tatiana; Costedoat-Chalumeau, Nathalie; Morel, Nathalie; Marozio, Luca; Tincani, Angela; Andreoli, Laura; Haladyj, Ewa; Meroni, Pier L.; Gerosa, Maria; Alijotas-Reig, Jaume; Tenti, Sara; Mayer-Pickel, Karoline; Simchen, Michal J.; Bertero, Maria T.; De Carolis, Sara; Ramoni, Véronique; Mekinian, Arsène; Grandone, Elvira; Maina, Aldo; Serrano, Fátima; Pengo, Vittorio; Khamashta, Munther A. (Thrombosis and Haemostasis, 2018)
The effect of additional treatments combined with conventional therapy on pregnancy outcomes was examined in high-risk primary antiphospholipid syndrome (PAPS) patients to identify the most effective treatment strategy. The study's inclusion criteria were (1) positivity to lupus anticoagulant alone or associated with anticardiolipin and/or anti-β2 glycoprotein I antibodies; (2) a history of severe maternal–foetal complications (Group I) or a history of one or more pregnancies refractory to conventional therapy leading to unexplained foetal deaths not associated with severe maternal–foetal complications (Group II). Two different additional treatments were considered: oral—low-dose steroids (10–20 mg prednisone daily) and/or 200 to 400 mg daily doses of hydroxychloroquine and parenteral—intravenous immunoglobulins at 2 g/kg per month and/or plasma exchange. The study's primary outcomes were live birth rates and pregnancy complications. A total of 194 pregnant PAPS patients attending 20 tertiary centres were retrospectively enrolled. Hydroxychloroquine was found to be linked to a significantly higher live birth rate with respect to the other oral treatments in the Group II patients. The high (400 mg) versus low (200 mg) doses of hydroxychloroquine (p = 0.036) and its administration before versus during pregnancy (p = 0.021) were associated with a significantly higher live birth rate. Hydroxychloroquine therapy appeared particularly efficacious in the PAPS patients without previous thrombosis. Parenteral treatments were associated with a significantly higher live birth rate with respect to the oral ones (p = 0.037), particularly in the Group I patients. In conclusion, some additional treatments were found to be safe and efficacious in high-risk PAPS pregnant women.
Keywords: antiphospholipid syndrome; hydroxychloroquine; low-dose steroids; intravenous immunoglobulins; plasma exchange